Pembuatan Aplikasi Sistem Alat Pengunci Pintu Berbasis Solenoid Pada Sistem Monitoring Kelas (Smoke) - Naufal Fadhullah; Rahmat Hidayat (Jurnal Ilmiah Wahana Pendidikan, 2022)
Making an application requires a software to support its creation, for example Android Studio and MIT App Inventor. The advantage of MIT App Inventor compared to Android studio is that there is no need to use a qualified laptop/PC specification because MIT App Inventor Inventor is available on Google and use a gmail account to register. Furthermore, the advantage of MIT App Inventor is that it does not require a programming language in its manufacture, which is like a puzzle. This application has several features in it, namely it can see whether the class has been used or not. Furthermore, this application has a class reservation feature that can make it easier to use the class. This application can support the 5.1 Lollipop operating system up to the latest version. The results of the research on the development of a class monitoring system application (SMOKE) are in the Very Eligible category because it meets the aspects of Functionality 100% (very feasible), Efficiency 88% (very good), Usability 87.6% (very feasible), and Portability of 100% ( very worthy).